Living Organ Donation by Minors: An Analysis of the Regulations in European Union Member States. Issue 12 (13th July 2016) - Thys, K.; Van Assche, K.; Nys, H.; Sterckx, S.; Borry, P.
Abstract : Living organ donation (LD) is an increasingly established practice. Whereas in the United States and Canada LD by minors has occasionally been reported, LD by minors seems to be largely absent in the European Union (EU). It is currently unclear whether this is the result of a different legal approach. This study is the first to systematically analyze the regulations of EU member states, Norway, and Iceland toward LD by minors. Relevant regulations were identified by searching government websites, translated, compared, and sent for verification to national legal experts. We identified five countries where LD by minors is allowed. In two of these (Belgium and the United Kingdom), some minors may be deemed sufficiently mature to make an autonomous decision regarding LD. In contrast, in the three other countries (Luxembourg, Norway, and Sweden), LD by minors is only allowed subject to parental permission and the assent (or absence of objection) of the donor. Where allowed, regulations differ significantly with regard to the substantive and procedural safeguards in place. In view of the controversial nature of the procedure, as illustrated by recent reports and surveys, we argue for a very cautious approach and greater harmonization in countries where LD by minors is allowed. Abstract : A systematic analysis of the transplant regulations of the 28 member states of the European Union, Norway and Iceland reveals that only five countries allow living organ donation by minors, which may explain why this practice is largely absent in Europe.